A Rare Case of Complicated Sinonasal Meliodosis Mimicking Sinonasal Lymphoproliferative Disease - Yuanzhi, Cheah; Hanzali, Jumastapha; Tang, Ing Ping (Springer Nature link, 2023)
Unilateral nasal obstruction with purulent nasal discharge is one of the presentations for sinonasal melioido-sis. However, it may mimic nasal NK/T cell lymphoma. Both causing tissue destruction involving nasal septum, lateral nasal wall and palate. Here, we report a case of disseminated melioidosis involving sinonasal mimicking nasal lymphoma in a 32-year-old immunocompetent lady. She presented with prolonged fever, unilateral nasal blockage, painful facial swelling and knee pain. Clinical findings revealed extensive necrotic tissue and crusting involving right lateral wall of nasal cavity. Tissue and blood culture and sensitivity (C + S) grew Burkholderia pseudomallei. Recovery was complete after surgery and antibiotics.